Developing Substance Use Programming for Person-Oriented Recovery and Treatment (SUPPORT): protocol for a pilot randomized controlled trial - Dennis P. Watson; Bradley Ray; Lisa Robison; Huiping Xu; Rhiannon Edwards; Michelle P. Salyers; James Hill; Sarah Shue (Pilot and Feasibility Studies, 2017)
Abstract Background There is a lack of evidence-based substance use disorder treatment and services targeting returning inmates. Substance Use Programming for Person-Oriented Recovery and Treatment (SUPPORT) is a community-driven, recovery-oriented approach to substance abuse care which has the potential to address this service gap. SUPPORT is modeled after Indiana’s Access to Recovery program, which was closed due to lack of federal support despite positive improvements in clients’ recovery outcomes. SUPPORT builds on noted limitations of Indiana's Access to Recovery program. The ultimate goal of this project is to establish SUPPORT as an effective and scalable recovery-oriented system of care. A necessary step we must take before launching a large clinical trial is pilot testing the SUPPORT intervention. Methods The pilot will take place at Public Advocates in Community Re-Entry (PACE), nonprofit serving individuals with felony convictions who are located in Marion County, Indiana (Indianapolis). The pilot will follow a basic parallel randomized design to compare clients receiving SUPPORT with clients receiving standard services. A total of 80 clients within 3 months of prison release will be recruited to participate and randomly assigned to one of the two intervention arms. Quantitative measures will be collected at multiple time points to understand SUPPORT’s impact on recovery capital and outcomes. We will also collect qualitative data from SUPPORT clients to better understand their program and post-discharge experiences. Discussion Successful completion of this pilot will prepare us to conduct a multi-site clinical trial. The ultimate goal of this future work is to develop an evidence-based and scalable approach to treating substance use disorder among persons returning to society after incarceration. Trial registration ClinicalTrials.gov (Clinical Trials ID: NCT03132753 and Protocol Number: 1511731907). Registered 28 April 2017.